Pengaruh Penanaman Modal dalam Negeri dan Inflasi terhadap Indeks Pembangunan Manusia dengan Produk Domestik Bruto sebagai Variabel Intervening Periode 2015–2024 - Nurul Azka Albanjari; Emmy Indrayani (Journal of Innovative and Creativity, 2026)
Sustainable economic development is not solely reflected by economic growth but also by improvements in human development outcomes. This study aims to examine the effect of Domestic Investment (Penanaman Modal Dalam Negeri/PMDN) and inflation on the Human Development Index (HDI), with Gross Domestic Product (GDP) serving as an intervening variable in Indonesia during the period 2015–2024. This research employs a quantitative approach using annual time-series secondary data, analyzed through multiple linear regression and Sobel mediation tests. The results indicate that domestic investment has a significant effect on GDP, while inflation does not significantly affect GDP. Furthermore, GDP is found to have a significant effect on HDI, whereas domestic investment and inflation do not have a direct significant effect on HDI. The mediation analysis reveals that GDP significantly mediates the relationship between domestic investment and HDI, but does not mediate the effect of inflation on HDI. These findings suggest that improvements in human development in Indonesia are more effectively achieved through strengthening domestic investment that promotes sustainable economic growth.